2006
DOI: 10.1681/asn.2005020132
|View full text |Cite
|
Sign up to set email alerts
|

Serum β-2 Microglobulin Levels Predict Mortality in Dialysis Patients

Abstract: In the randomized Hemodialysis (HEMO) Study, chronic high-flux dialysis, as defined by higher beta-2 microglobulin (beta(2)M) clearance, compared with low-flux dialysis did not significantly alter all-cause mortality in the entire cohort but was associated with lower mortality in long-term dialysis patients. This analysis examined the determinants of serum beta(2)M levels and the associations of serum beta(2)M levels or dialyzer beta(2)M clearance with mortality. In a multivariable regression model that examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
315
3
20

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 396 publications
(351 citation statements)
references
References 28 publications
13
315
3
20
Order By: Relevance
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…In the HEMO Study, membrane flux was defined by the clearance of ␤ 2 M, taken as a surrogate for the clearance of middle molecules. As a result of the higher clearance, the cumulative mean predialysis serum ␤ 2 M level during follow-up in the high-flux arm was statistically significantly lower than that in the low-flux arms (33.6 versus 41.5 mg/L) (5). Further secondary analysis of the data showed that predialysis serum ␤ 2 M levels predicted allcause mortality in the HEMO Study cohort, with an 11% increase in mortality for each 10-mg/L increase in ␤ 2 M level, even after adjustment for years on dialysis and residual kidney function (5).…”
mentioning
confidence: 82%
“…The dialyzers used, frequency of serum sample collection for ␤ 2 M, and calculation of clearances and Kt/V of ␤ 2 M in the HEMO Study were previously reported (2,5,10). The criteria for high-flux dialyzers were an ultrafiltration coefficient Ն14 ml/h per mmHg and a ␤ 2 M clearance Ͼ20 ml/min averaged over the lifespan of the dialyzer during clinical dialysis.…”
Section: Dialyzers and Dialysatesmentioning
confidence: 99%
See 2 more Smart Citations